Da dominação masculina à submissão feminina: relação amorosa de adolescentes infratores e suas companheiras - Ferro, Viviane de Souza (2009)
The aim of this study is to understand the romantic relationship choice of couples consisting of male adolescents who have committed criminal offenses and their female partners, as well as the continuation of the relationship after the determination of socio-educational measures of deprivation of freedom, through the identification of the relationship patterns found in the families of each of the members of the couple. Two couples in a government instituion of Distrito Federal that carries out such measures were studied from a qualitative perspective. Individual interviews were performed with each member of the couple and a genogram was constructed. The results showed that the family plays a fundamental part in the transmission and repetition of male and female roles in the romantic relationship and in the establishment of communication styles and rules. With regard to gender issues, the relationships of the couples are based on a patriarchal model in which the man exercises his power and domination while the woman focuses on affective, care, and obedience relationships, even when the adolescent is institutionalized